Wildwood Creek - Wingate, Lisa (Bethany House, a division of Baker Publishing Group, 2014)
"While working as a costuming assistant on a docudrama, Allie Kirkland has discovered strange connections between herself and a teacher who disappeared a century ago in the legendary frontier settlement of Wildwood. Is history about to repeat itself?"--